Dinâmica termo-hídrica do solo em função da cobertura vegetal no Semiárido brasileiro - Silva, Jailson Medeiros (2022)
Solar radiation is the primary source of energy for processes taking place in the earthatmosphere system. Through solar radiation, soil temperature influences chemical, physical, and biological factors and is a key parameter affecting changes in the balance between water flow, energy flow, and ecological stability. The objective was to evaluate the dynamics of soil temperature and water content subjected to four types of vegetation cover. The experiment was developed in four areas (moringa plantation; angico plantation; native caatinga and exposed soil) at Fazenda São Gabriel, in the municipality of São José de Espinharas, PB. The research was carried out from May 19th to 25th, 2021. Data were collected daily on soil temperature at three depths (0; 7.5 and 15 cm), soil water content, wind direction, wind speed, ambient temperature, relative humidity, rainfall and light intensity. All the variables mentioned above were collected at 6 am, 9 am, 12 noon, 3 pm, and 6 pm. Data on soil temperature and water content were submitted to analysis of variance and Tukey's test at 5% significance using SAS/STAT 9.3 software (2011). Soil temperature data were also submitted to regression analysis. The data were also submitted to principal component analysis (PCA) and cluster analysis, using R software. Furthermore, Pearson correlation analysis was performed among the several variables collected using the PaST software. A positive correlation was found between: wind speed and light; air humidity and rainfall; ambient temperature and soil temperature; and a negative correlation between air humidity and soil temperature; air humidity and ambient temperature; rainfall and soil temperature; rainfall and ambient temperature. The most frequent wind direction in the area occurred from the southeast direction. The presence of vegetation keeps more water in the soil and provides lower temperature ranges compared to bare ground. Planted areas have higher surface temperatures, but provide thermal stability in the underlying layers. The temperature in the caatinga area showed less temperature variation throughout the day, differing from the other areas.